The Anthill murders / Hans Olav Lahlum ; translated from the Norwegian by Kari Dickson. - Lahlum, Hans Olav, 1973- (Lahlum, Hans Olav, 1973- Kolbjorn Kristiansen, 2017)
1972. Across Oslo, a serial killer is hunting down young women. Each victim found strangled and with a peculiar calling-card placed upon their bodies: a cut-out picture of an ant. The first victim is a timid theology student, the next a jazz singer, followed by the heir to one of the largest fortunes in Oslo. But despite Inspector K2's best efforts to find a link, the only thing connecting them seems to be their murder. With his assistant Patricia's intellect put to the test, and increasing pressure from his boss as the clock ticks down to the next possible killing, K2 is in danger of losing his position as Oslo's leading homicide detective ...